Disaggregating How Asian Americans Define a Healthy Diet: Exploring Generational and Intra-family Differences Through Dyadic Interviews. (14th June 2022) - Cai, Julia; Ali, Shahmir; Mohsin, Farhan; Parikh, Roshan; Yang, Katherine; Auer, Sian; Sanghvi, Ananya; Kamal, Fatema; Merdjanoff, Alexis; Parekh, Niyati; DiClemente, Ralph
Abstract: Objectives: Asian Americans (AAs) experience a complex and growing non-communicable disease burden linked with dietary behaviors. Dietary norms, which significantly contribute to eating behaviors, face a complex set of Western and Asian socio-ecological influences in AA communities. However, little is known of how dietary norms (such as definitions of a "healthy diet") are transmitted, intersect, and differ in a multigenerational family environment. Methods: AA young adults and family members were recruited to participate in dyadic, 60-minute Zoom interviews (Jun - Dec 2021). Young adults and family members were interviewed separately on their respective eating behaviors, including perceived definition of a healthy diet. Recordings were inductively analyzed to identify themes related to different facets of a conceptualized healthy diet. Results: A total of 41 AAs were interviewed (76% female, 61% US-born, age 19–69), including 20 young adults and 21 family members (10 parents, 9 siblings, 2 cousins). Diet healthfulness was defined in three dimensions: types of food, cooking methods, and intersection of diet with holistic wellbeing. Young adults consistently emphasized the role of their parents in shaping their idea of a healthy diet, particularly Asian-specific conceptualizations of balance (e.g., "yeet hay"). However, while these ideas were particularly influential among older participants, younger participants also emphasized the intersection of diet with emotional and spiritual well-being. Both stressed cooking methods as indicators of healthfulness. While a "healthy diet" was conceptualized through intake of food groups such as fruits, vegetables, and proteins, foreign-born and older participants put a larger emphasis on dietary restrictions (e.g., completely cutting out food groups, such as fast food), while US-born and younger participants stressed enjoying foods in moderation. Conclusions: The differential understanding and impact of AA norms related to diet healthfulness highlights the need for a disaggregated understanding of dietary attitudes and behaviors in health-based interventions for AAs of different generations, particularly family-based programs. Findings call for future mixed-methods research to explore the complex dietary norms identified. Funding Sources: South Asian Health and Research Group (SAHARA).